Investigating the migratory movement of Humpback Whales (Megaptera novaeangliae) between Husavik, Iceland and Greenland using photo-identification - Morin, Kelly Pauline, 1992- (2019)
Verkefnið er lokað til 28.05.2020. Humpback whales have long migratory routes. They move from low latitude breeding grounds to high latitude feeding grounds on an annual basis and tend to show a large degree of site fidelity towards the latter. In the North Atlantic, main feeding aggregations include the Gulf of Maine, the Gulf of St. Lawrence, Newfoundland and Labrador, West Greenland, East Greenland, Iceland and Norway. This thesis aimed to explore the movement of humpback whales between three of those locations, namely West Greenland, East Greenland and Husavik, Northeast Iceland. This information can aid in monitoring the status of the species as well as managing anthropogenic activities that could impact marine life. By using existing photo-identification catalogues between these three locations, it was determined that there was very little mixing with only one match found between West Greenland and Husavik. These results suggest that only a small percentage of humpbacks are moving between these feeding grounds. While these results are congruent with current background literature, the possibility of future mixing is growing, especially in light of worsening climate change issues. Finally, this thesis provides a comparative analysis on the current methods for humpback photo-identification comparison studies and suggests recommendations for a more standardised system.